Analisis Sanitasi Dasar Wilayah Pesisir Dusun Talaga Ratu - Sunik Cahyawati (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2023)
Coastal communities are a group of people who live together inhabiting coastal areas and then form and have a distinctive culture related to their dependence on the use of coastal resources. Basic sanitation is a minimum environmental health requirement that every family must have to meet their daily needs. The scope of basic sanitation is the provision of clean water, disposal of household waste, provision of healthy latrines and clean water facilities. The purpose of this research is to identify basic sanitation in Waitasi Hamlet. The type of research method used is descriptive observation research. Based on the results, it can be concluded that clean water facilities with clean water supply facilities in the Waitasi Hamlet community which have their own, odorless, colorless, tasteless as much as 1 4 KK (93.3%). facilities for the availability of clean water that are not their own, odorless, colorless, tasteless as much as 1 family (6.7%). Family latrine facilities in the Waitasi hamlet community have not met the requirements for providing family latrines that are not in the form of a goose neck and have a septic tank of 10 families (66.7%). for latrines that are not swan neck, and have a lid, channeled to the river/kolam are 2 families (13.7%) and for latrines with a goose neck saptic tank it is 1 household (6.7%). Waste water disposal facilities in the Dusun Waitasi community do not meet the SPAL requirements and are channeled into open sewers as many as 6 people (40.0%), who have impregnated and do not pollute water sources (distance to water source >10 meters) as many as 6 people (40.0) , and 3 people who have SPAL and have closed sewers (City Channels) for further processing (20.0%). Most of the waste disposal facilities in the Dusun Waitasi community do not meet the requirements, namely 11 families (73.3%). people do not have waste disposal facilities and tend to use plastic bags, sacks and boxes for temporary disposal and then throw them to the beach and rivers. there are 4 families (36.7) that have garbage disposal facilities but are not watertight.